SYNTAX: THE SRUCTURE AND FUNCTION OF SENTENCE FORMATION IN ENGLISH STRUCTURE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the concept of syntax as a core component of English grammar, focusing on its role in sentence formation and linguistic coherence. Syntax governs how words are structured and ordered within a sentence, enabling clear communication and proper understanding. The paper outlines key syntactic rules in English, including sentence structure, word order, and subject-verb agreement. It also highlights the importance of syntax in language acquisition and communication. By understanding syntactic patterns, learners can improve both their written and spoken English skills. This study emphasizes that mastering syntax is vital for achieving linguistic accuracy and fluency.